Effect of Body Mass Index on Outcomes after Prepectoral Breast Reconstruction. Issue 3 (September 2019) - Gabriel, Allen; Sigalove, Steven; Sigalove, Noemi M.; Storm-Dickerson, Toni L.; Pope, Nicole; Rice, Jami; Maxwell, G. Patrick
Abstract : Background: Body mass index has been shown to be a predictor of outcomes after subpectoral expander/implant reconstruction, with every unit increase in body mass index increasing the risk of complications by approximately 6 percent. The effect of body mass index on complications after prepectoral reconstruction has not yet been evaluated and is the purpose of this study. Methods: A total of 366 reconstructed breasts from 197 patients were stratified into five body mass index groups (normal; overweight; and class I, class II, and class III, obese) and postoperative complications were compared across the groups. Additional analyses were performed using broad classifications of body mass index into nonobese and obese in addition to normal, overweight, and obese. Body mass index as an independent predictor of complications was assessed using multivariate logistic regression analysis. Results: Complication rates did not differ significantly across body mass index groups when using the broad classifications. With five-group stratification, significantly higher rates of return to operating room, expander/implant loss, skin necrosis, wound dehiscence, and overall complications were seen in class II and/or class III obese versus overweight patients. However, on multivariate logistic regression analyses, body mass index, as a continuous variable, did not independently predict any complication. Diabetes and smoking emerged as significant predictors of any complication, indicating that these factors, rather than body mass index, were driving the increased rates of complications seen in the high–body mass index groups. Conclusion: Body mass index alone is not a predictor of outcomes after prepectoral expander/implant breast reconstruction and should not be used to estimate risk of postoperative complications or exclude patients for prepectoral reconstruction. CLINICAL QUESTION/LEVEL OF EVIDENCE: Risk, II.